2014
DOI: 10.1007/s13193-014-0345-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hybrid Verrucous Carcinoma: A Clinical Study

Abstract: Hybrid Verrucous Carcinoma is an uncommon tumour wherein Verrucous Carcinoma (VC) is coexisting with conventional Squamous Cell Carcinoma (SCC) within same maternal field. The heterogeneous nature, infrequency of occurrence and the difficulties associated with diagnosis and management of this tumor is discussed through a retrospective study. Patients of primary hybrid VC treated from Jan 2010 to May 2013 at a tertiary institute were analyzed on multivariate cox regression model. During the above mentioned peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Oral hybrid verrucous carcinoma (VC) is a neoplasm composed of OVC and differently-differentiated OSCC (85). For example, welldifferentiated OSCC was identified within OVC and invaded the underlying connective tissue and bone (76).…”
Section: Ovc and Oral Squamous Papilloma (Osp)mentioning
confidence: 99%
“…Oral hybrid verrucous carcinoma (VC) is a neoplasm composed of OVC and differently-differentiated OSCC (85). For example, welldifferentiated OSCC was identified within OVC and invaded the underlying connective tissue and bone (76).…”
Section: Ovc and Oral Squamous Papilloma (Osp)mentioning
confidence: 99%
“… 33 Although multiple biopsies from different areas of the tumour might be helpful to identify invasive component, surgical excision and histopathological examination of whole resection specimen is needed for definitive diagnosis. 32 If hybrid verrucous carcinoma is recognized, the pathologist should quantitate each component of the tumour, define the degree of differentiation of the conventional SCC component and comment on depth of the tumour invasion, potential presence of lymphatic or perineural invasion and the adequacy of the resection margins. These features help the clinicians to decide about adjuvant treatment options.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Moreover, examination of small tumour samples obtained with biopsy could be misleading as an invasive component is often missed at sampling. 32 Gokavarapu et al reported that 51% of cases preoperatively diagnosed as oral FIGURE 1. Verrucous carcinoma of the right buccal mucosa (clinical stage T2N0M0) in an 81-year-old male patient.…”
Section: Clinical Presentationmentioning
confidence: 99%